Struggles for distinction: Classing as discursive process in UK museum work. Issue 3 (13th April 2020) - Evans, Samantha; Whiting, Rebecca; Mackenzie Davey, Kate
Abstract : This article responds to calls from critical diversity scholars to explore class in context, arguing for a view of classing as a discursive process and adopting Bourdieu's concept of field as a site of discursive struggle. Analysing interview, web and focus group data, we address this in the field of UK museum work. We contextualize the field's dynamic nature, highlighting its state of flux and explore three discourses: distinguishing the field; disavowing the market; and gaining recognition through which it is constituted, and classing practised. Discursive strategies of reinforcing, reframing and re‐valorizing were deployed by participants to legitimate their own and other positions in the field. We show how classing is a core process constituting an occupational field, how museum workers are entrapped by and complicit in this process, and conclude with wider implications for understandings of class, classed inequality and diversity.